Rapid and Sensitive Assay of Helicobacter pylori With One-Tube RPA-CRISPR/Cas12 by Portable Array Detector for Visible Analysis of Thermostatic Nucleic Acid Amplification - Dai, Bing; Xiang, An; Qu, Di; Chen, Guo; Wang, Li; Wang, Wenwen; Zhai, Dongsheng; Wang, Lei; Lu, Zifan (Frontiers in Microbiology, 2022)
Helicobacter pylori (H. pylori) has infected more than half of the world's population and is still a threat to human health. The urea breath test, despite being widely used in clinical diagnosis, still faces huge challenges in the immediate detection of H. pylori. Thus, a rapid, sensitive, and highly specific point of care diagnosis is particularly important for preventing the further transmission of H. pylori, as well as for real-time monitoring of the disease in a given population. Recently, the clustered regularly interspaced short palindromic repeats (CRISPR) based diagnostics have been applied to various types of nucleic acid testing, however, there are often shortcomings of complex operation and high signal transmission background. Herein, we proposed a new platform for the assay of H. pylori using one- tube-based CRISPR/Cas12a diagnostic methods and designed a detector for this platform, which is a portable array detector for visual analysis of thermostatic nucleic acid amplification (Pad-VATA). By incorporating isothermal recombinase polymerase amplification, our platform could detect the conserved gene fragments of H. pylori with a constant low as 2 copies/µL. The assay process can be performed at a single temperature in about 30 min and integrated into the reactor in the palm-sized Pad-VATA to facilitate rapid diagnosis of H. pylori. We also verified the accuracy of our platform using 24 mimicked clinical samples, and found that the platform can quickly detect H. pylori infection in a given population. We believe that this fast, convenient, efficient, and inexpensive screening and diagnostic platform can be widely used in various settings, including homes and clinics.